Hubungan Pengetahuan Triage Perawat dengan Lama Bekerja di Puskesmas: A Cross-Sectional Study: Relationship Between Nurses’ Triage Knowledge and Length of Service in Community Health Centers: A Cross-Sectional Study - Suwardianto, Heru; Alfianto, Ahmad Guntur; Amaral, Octavio Daniel Bria; Vijay, P Vijay; Kumar, K. Sesha (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
Emergency and disaster situations demand rapid, accurate, and well-coordinated responses from healthcare professionals. Triage is a critical process for prioritizing patients based on severity, ensuring optimal use of limited medical resources. Nurses are often the first responders responsible for triage implementation, especially in community health centers (Puskesmas) in Indonesia. Knowledge of triage systems, particularly the Simple Triage and Rapid Treatment (START) method, is essential for achieving optimal patient outcomes. This study aimed to examine the relationship between nurses’ triage knowledge and length of service in community health centers, providing insights for targeted training and emergency preparedness strategies. A cross-sectional correlational study was conducted with 32 nurses from 19 community health centers in Cirebon, Indonesia, selected through purposive sampling. Triage knowledge was assessed using a validated 16-item questionnaire, with scores categorized into low, moderate, and high. Length of service was measured in years. Data were collected via an online session and analyzed using descriptive statistics and Pearson correlation analysis with a significance level of p < 0.05. Most nurses demonstrated high triage knowledge (75%) with a mean score of 13.0 ± 2.74. Knowledge was highest in disaster definitions (93.8%) and START triage concepts (93.8%), while the most errors occurred in identifying green-labeled (68.8% incorrect) and white-labeled patients (59.4% incorrect). Pearson correlation showed a weak, non-significant positive relationship between length of service and triage knowledge (r = 0.083; p = 0.650). The findings indicate that length of service alone does not ensure higher triage knowledge, especially in community health centers with limited exposure to emergencies. Continuous professional development, scenario-based simulations, and structured training are essential to maintain and enhance nurses’ triage competence. These results can inform the development of targeted educational programs and policies to strengthen emergency preparedness in primary healthcare settings.